Exploring the Subnational Dimension of Income Inequality: An Analysis of the Relationship between Inequality and Electoral Turnout in the Developed Countries - Vincent A. Mahler (Luxembourg Income Study (LIS), 2002)
This paper offers an exploratory analysis of the subnational dimension of income inequality, using data from the Luxembourg Income Study. The paper undertakes two basic tasks. First, it describes the results of calculations on household-level income data that produce indicators of intra- and inter-household inequality for 191 regions in 12 developed countries for the late 1980s and early 1990s, and for 149 regions in 8 countries for the mid-1990s. Second, the paper demonstrates the value of regional analysis by re-examining the relationship between electoral turnout and income inequality, an important substantive issue which has heretofore been explored almost entirely at the national or individual level but upon which regional-level analysis can shed valuable light.
Keywords: 330; Regionale Einkommensverteilung; Wahlverhalten; Industrieländer